Importance of Forecasts in decision making in MSMEs (GEON Journal (Management, Organizations and Business), 2018)
The study of forecasts as elements in decision making in companies have greater areas of opportunity within organizations, this is because the forecasts help decision makers to make more precise judgments about future events and In this part, mathematics turns out to have an important role, as mentioned (Wilson & Koerber, 1992) it has been shown that quantitative methods are useful to make better predictions about the future course of events, so it has been created the need for new software to be developed through the use of the computer these predictions are generated more quickly, but it is fundamental to understand well how the calculations are made manually to later use these computational tools.For the purposes of knowledge that the administrator requires to know about the different methods of forecasts and thus select the one that complies with the internal objectives, the author Farrera Gutiérrez (2012) divides them into: Qualitative Methods among which are: Delphi Methods, Historical Analogy and Market Research. Within the Quantitative Methods are: Moving Average, Exponential Smoothing and Linear Regression. It is important to note that knowing the different forecasting methods allows the decision maker in front of a MSME, to get as accurate as possible about the behavior of the data on which their future estimates are generated.
Keywords: Forecasts; Organizations; Decision making